Olfactory neuroblastoma: diagnosis, management, and current treatment options - Tosoni, Alicia; Di Nunno, Vincenzo; Gatto, Lidia; Corradi, Giacomo; Bartolini, Stefania; Ranieri, Lucia; Franceschi, Enrico (Frontiers in Oncology, 2023)
Olfactory neuroblastoma (ONB) is a rare neoplasm originating from the olfactory neuroepithelium representing 3-6% of tumors of the sinonasal tract. ONB require multi-disciplinary care. Historically, the gold standard surgical procedure for ONB has been open craniofacial resection. In the last years, endoscopic endonasal approaches have been largely introduced with lower complication rates, shorter hospital stay, and similar clinical outcome. Radiotherapy plays an important role in the management of ONB, however there are not generally accepted recommendations for its application. Although there is agreement that multimodal therapy is needed, the optimal use of chemotherapy is still unknown. The rarity of the disease, makes difficult to draw definitive conclusions about the role of systemic treatment in induction and concomitant setting.